(untitled) (Rudarsko-geološko-naftni zbornik, 2015)
Brief review of Chapter’s activities throughout Academic Year is given in this Article. By introducing new ways of activities this Academic Year, number of members has greatly incresed which will help to develop Chapter in different areas. Organizing of Annual Student Energy Conference is still the main focus of Chapter’s activities.